Facial representation of paroxysmal hemicrania and associated temporomandibular disorder: a case report - Pamela Pessoa Maia dos Santos; Juliana Araújo Oliveira Buosi; Pedro Braga Neto; Hellíada Vasconcelos Chaves; Paulo César Rodrigues Conti; Lívia Maria Sales Pinto Fiamengui (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Paroxysmal Hemicrania is a trigeminal autonomic cephalalgia described as a severe and strictly unilateral pain, which occurs in paroxysms at orbital, supraorbital and/ or temporal region. A 45-year-old woman presented to an orofacial pain specialist reporting severe, burning, throbbing, strictly right-sided headache associated to ipsilateral autonomic symptoms and orofacial pain. The pain was perceived on the maxillary region followed by pain spread to the head. Interdisciplinary evaluation, along with absolute responsiveness to indomethacin and normal Brain Magnetic Resonance imaging, led to the diagnosis of primary Episodic paroxysmal hemicrania with facial representation and myofascial pain of masticatory muscles. Dentists should be aware of paroxysmal hemicrania with facial representation and the possibility of temporomandibular disorder coexistence, in order to avoid misdiagnosis and inadequate management. Paroxysmal hemicrania may be first perceived on the face and may be associated with interparoxysmal pain. In these cases, efficient anamnesis and clinical evaluation followed by interdisciplinary approach is needed.